Love me or leave me [videorecording (DVD)] - Vidor, Charles, 1900-1959; Day, Doris, 1922-2019-; Cagney, James, 1899-1986; Mitchell, Cameron, 1918-1994 (Warner Bros. Entertainment : Distributed by Warner Home Video, 2005)
Jazz age singing sensation Ruth Etting had it all, but it took more than talent to make it big. Her rise to fame at the hands of her Chicago gangster boyfriend turned her life off stage into a world of fear and abuse.